Тепловой контроль источника резервного питания ИРП-02 - Корниенко, Е. В.; Шевченко, М. А. (ХНУРЭ, 2012)
Applicability of non-contact thermal control of electronics industry products and its advantages are confirmed experimentally. The results of the thermal control of backup power source are given. Overheated areas related to the deterioration of contact soldered of electronic circuit components are found
Keywords: тепловой контроль; источник резервного питания